Keterkaitan Peluang Investasi, Hutang dan Kebijakan Dividen - Herry Subayo; Toto Suharmanto (Jurnal Bisnis dan Ekonomi, 2018)
Dividend decisions must consider many aspects, not only liquidity positions but also related to behavioral problems. This study examines the role of investment opportunities and debt in influencing dividend policy. the model developed puts investment opportunities and debt as moderating variables. The sample used is non-financial companies listed on the IDX of 2011-2013, while the sampling technique uses purposive sampling. Findings, investment opportunities and debt are proven to weaken the role of profitability in determining dividends. This finding is very phenomenal, that the level of debt in the non-financial industry has level number that can affect dividend payments. based on the level of debt, investment decisions as a realization of the availability of investment opportunities tend to use internal source.